QTL identification for cassava bacterial blight resistance under natural infection conditions - Soto Sedano, Johana; Mora Moreno, Rubén Eduardo; Calle, Fernando; López Carrascal, Camilo Ernesto (Universidad Nacional de Colombia, 2017)
Cassava, *Manihot esculenta* Crantz, represents the main food source for more than one billion people. Cassava's production is affected by several diseases, one of the most serious is cassava bacterial blight (CBB) caused by *Xanthomonas axonopodis* pv. *manihotis* (*Xam*). A quantitative trait loci (QTL) analysis for CBB resistance was performed under natural infection conditions, using a mapping population of 99 full-sibs genotypes highly segregant and a SNP-based high dense genetic map. The phenotypic evaluation was carried out in Puerto López, Meta, Colombia, during the rainy season in 2015. Both resistant and susceptible transgressive segregants were detected in the mapping population. Through a non-parametric interval mapping analysis, two QTL were detected, explaining 10.9 and 12.6 % of phenotypic variance of resistance to field CBB. After a bioinformatics exploration four genes were identified in the QTL intervals. This work represents a contribution to the elucidation of the molecular bases of quantitative cassava resistance to *Xam*.